Mechanism for phosphorus removal from wastewater with fly ash of municipal solid waste incineration, Seoul, Korea. (20th January 2021) - Gu, Shuai; Fu, Bitian; Ahn, Ji-Whan; Fang, Baizeng
Abstract: A novel mechanism that combines adsorption with chemical precipitation is proposed to interpret the removal of phosphorus with fly ash of municipal solid waste incineration. Thermodynamic modeling results demonstrate the vital roles of both Ca 2+ and OH − in the chemical precipitation process. The mechanism is dominated by precipitation at low phosphorus concentrations, while under high phosphorus concentrations it is under a mixed control by precipitation and adsorption in the filtered solution of fly ash. By subtracting the thermodynamic modeling value of precipitation at certain equilibrium pH from the total removal rate at the corresponding pH, the contribution of adsorption to the total phosphorus removal is calculated for the first time in the fly ash solution. The removal process of phosphorus with calcium-containing waste materials under ambient atmosphere may involve coupled reactions between Ca(OH)2 dissolution, chemical precipitation of hydroxyapatite, adsorption of phosphorus on the surface, and carbonation. The removal efficiency peaks in the CO2 -free atmosphere with 100% phosphate removal and 98.9% carbonate removal. Graphical abstract: Image 1 Highlights: Thermodynamic modeling is used to predict the precipitation of P in aqueous solution. Both precipitation and adsorption mechanisms are utilized to explain the removal of P. Contribution of adsorption is calculated by modeling and experimental results. Removal mechanism is precipitation and mixed-controlled depending on P concentration. Removal efficiency decrease with prolonged contact time is caused by contacting CO2 .